Imaging Brain Glx Dynamics in Response to Pressure Pain Stimulation: A 1H-fMRS Study - Jelen, Luke A.; Lythgoe, David J.; Jackson, Jade B.; Howard, Matthew A.; Stone, James M.; Egerton, Alice (Frontiers in Psychiatry, 2021)
Glutamate signalling is increasingly implicated across a range of psychiatric, neurological and pain disorders. Reliable methodologies are needed to probe the glutamate system and understand glutamate dynamics in vivo. Functional magnetic resonance spectroscopy (1H-fMRS) is a technique that allows measurement of glutamatergic metabolites over time in response to task conditions including painful stimuli. In this study, 18 healthy volunteers underwent 1H-fMRS during a pressure-pain paradigm (8 blocks of REST and 8 blocks of PAIN) across two separate sessions. During each session, estimates of glutamate + glutamine (Glx), scaled to total creatine (tCr = creatine + phosphocreatine) were determined for averaged REST and PAIN conditions within two separate regions of interest: the anterior cingulate cortex (ACC) and dorsal ACC (dACC). A two-way repeated measures analysis of variance determined a significant main effect of CONDITION (p = 0.025), with higher Glx/tCr during PAIN compared to REST across combined sessions, in the dACC ROI only. However, increases in dACC Glx/tCr during PAIN compared to REST showed limited reliability and reproducibility across sessions. Future test-retest 1H-fMRS studies should examine modified or alternative paradigms to determine more reliable methodologies to challenge the glutamate system that may then be applied in patient groups and experimental medicine studies.